2000
DOI: 10.1177/10454411000110010201
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Molecular Genetics on Oral Health Paradigms

Abstract: As a result of our increased understanding of the human genome, and the functional interrelationships of gene products with each other and with the environment, it is becoming increasingly evident that many human diseases are influenced by heritable alterations in the structure or function of genes. Significant advances in research methods and newly emerging partnerships between private and public sector interests are creating new possibilities for utilization of genetic information for the diagnosis and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 183 publications
1
32
0
1
Order By: Relevance
“…The other aims were to compare the ICP group with the other affected groups, as previous embryological studies have indicated that CLP infants are etiologically and developmentally distinct from ICP group [17,18], and to compare males and females. [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The other aims were to compare the ICP group with the other affected groups, as previous embryological studies have indicated that CLP infants are etiologically and developmentally distinct from ICP group [17,18], and to compare males and females. [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A gradient of protein concentrations across the layer of growing enamel has been observed (Hu et al 1997;Uchida et al 1997;Nanci et al 1998). Clinical and genetic features suggest that many direct and indirect factors contribute to enamel formation (Hart et al 2000;Downey et al 2002). Enamel formation is impaired if the bulk matrix proteins amelogenin, enamelin or ameloblastin or the enzyme enamelysin are absent or misexpressed (Lagerström et al 1991;Gibson et al 2001;Rajpar et al 2001;Mårdh et al 2002;Paine et al 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Cleft lip and palate (CLP) deformity has become a major public health problem affecting one in every 500 -1000 births worldwide [5]. Two most common types of CLP are cleft lip with or without cleft palate and a cleft palate only [1].…”
Section: Introductionmentioning
confidence: 99%